Guideline of Value and Earning Potential on Cultural Hand-Woven Cloth at Paoy Char village, Phnom Srok, Banteay Meanchey, Cambodia - sangvavann, khiev; Supannafai , Akkharadet; Sukantarat, Sureechai (Journal of Human and Society, Sisaket Rajabhat University, 2023)
This study investigated the production, sales, and earnings potential of culturally hand-woven cloth in Paoy Char village, Phnom Srok, Banteay Meanchey, Cambodia. The research revealed that silk and cotton were the primary materials used in production, employing traditional techniques throughout the manufacturing process. The distribution and pricing strategies were categorized into two types: those established by agencies and those by local groups. Furthermore, the product design aspect was classified into three distinct types. Earnings potential demonstrated variation among different groups and was contingent upon various factors, including organizational affiliations and marketing endeavors. In sum, the study suggests that these groups should prioritize enhancements in production processes, product design, distribution networks, and marketing campaigns to amplify their potential for higher earnings.